Identification of Copy Number Variation Among Nonsyndromic Cleft Lip and or Without Cleft Palate With Hypodontia: A Genome-Wide Association Study - Ghazali, Norliana; Abd Rahman, Normastura; Ahmad, Azlina; Sulong, Sarina; Kannan, Thirumulu Ponnuraj (Frontiers in Physiology, 2021)
Non-syndromic cleft lip and or without cleft palate (NSCL/P) with the present of hypodontia categorized as the common developmental abnormalities found in humans and animals. This study identified the genetic aberration involved in both NSCL/P and hypodontia pathogenesis. A cross-sectional study using genome-wide study copy number variation targeted CytoScan 750K array carried out on salivary samples from 61 NSCL/P and 20 non-cleft with and without hypodontia Malay subjects aged 7-13 yr old. Copy number variations (CNVs) of SKI and FHIT were identified in NSCL/P and non-cleft children using quantitative polymerase chain reaction (qPCR) as a validation analysis. Copy number calculated (CNC) for each gene determined with Applied Biosystems CopyCaller Software v2.0. The six significant CNVs included gains (12q14.3, 15q26.3, 1p36.32, and 1p36.33) and losses (3p14.2 and 4q13.2) in NSCL/P with hypodontia patients compared to the NSCL/P only. The genes located in these regions encoded LEMD3, IGF1R, TP73, SKI, FHIT, and UGT2β15. There were a significant gain and loss, of both SKI and FHIT copy number in NSCL/P with hypodontia compared to non-cleft group (p<0.05). The results supported that CNVs significantly furnish to the development of NSCL/P with hypodontia.